Solution of the weighted symmetric similarity transformations based on quaternions (vol 92, pg 1113, 2018) - Mercan, H.; Akyilmaz, O.; Aydin, C. (SPRINGER, 2018)
In the original article, Eq. (19), the covariance matrix of the source coordinates in the second term in the parenthesis.
Keywords: Geochemistry & Geophysics; Remote Sensing